1999
DOI: 10.1016/s0006-3495(99)77386-8
|View full text |Cite
|
Sign up to set email alerts
|

Stresses at the Cell-to-Substrate Interface during Locomotion of Fibroblasts

Abstract: Recent technological improvements in the elastic substrate method make it possible to produce spatially resolved measurements of the tractions exerted by single motile cells. In this study we have applied these developments to produce maps of the tractions exerted by 3T3 fibroblasts during steady locomotion. The resulting images have a spatial resolution of approximately 5 micrometers and a maximum intensity of approximately 10(2) kdyn/cm2 (10(4) pN/micrometers2). We find that the propulsive thrust for fibrobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

43
1,278
2
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,178 publications
(1,325 citation statements)
references
References 35 publications
43
1,278
2
2
Order By: Relevance
“…Ectopic LAMC2 expression or knockdown did not affect cell proliferation (all P40.05; Supplementary Figure S2A). Migrating cells exert traction force upon their surroundings, 26,27 and cell traction force is necessary in cancer cell migration and invasion. 28,29 Fourier transform traction microscopy showed that stably LAMC2-transfected A549R0 cells were bigger in size (Po0.05) and exhibited greater cell traction force (Figure 2e), with~1.5-fold higher (Po0.05) net contractile moment compared with mock control.…”
Section: Resultsmentioning
confidence: 99%
“…Ectopic LAMC2 expression or knockdown did not affect cell proliferation (all P40.05; Supplementary Figure S2A). Migrating cells exert traction force upon their surroundings, 26,27 and cell traction force is necessary in cancer cell migration and invasion. 28,29 Fourier transform traction microscopy showed that stably LAMC2-transfected A549R0 cells were bigger in size (Po0.05) and exhibited greater cell traction force (Figure 2e), with~1.5-fold higher (Po0.05) net contractile moment compared with mock control.…”
Section: Resultsmentioning
confidence: 99%
“…Further studies should concentrate on the subcellular mechanisms through which ␣-SMA increases fibroblast contractile activity and in particular investigate whether transfected ␣-SMA increases induces the formation of specialized focal contacts, typical for ␣-SMA-positive myofibroblasts (Dugina et al, 1998;Vaughan et al, 2000). For this purpose the use of embedded fluorescent beads in elastic polyacrylamide substrates (Pelham and Wang, 1997) in conjunction with detailed computer analysis (Dembo and Wang, 1999;Pelham and Wang, 1999) will be necessary. This technique can also allow to examine whether ␣-SMA expression mediates more efficient contraction by increasing the absolute contractile force or by optimizing the spatial distribution of several subcellular forces.…”
Section: Discussionmentioning
confidence: 99%
“…Forces exerted by hMSCs on MeHA substrates were measured via TFM, based on deformations in the substrate relative to the same substrate when relaxed, using a method developed by Dembo and Wang 53 . In this method, surface traction vectors generated by the cells on the underlying substrate were quantified by measuring embedded bead displacements and using known substrate properties (thickness, modulus) with custom-written software 53 . For this purpose, phase-contrast and corresponding fluorescent bead images were collected simultaneously using the microscope system described above.…”
Section: Methodsmentioning
confidence: 99%